0524 Impact of Novel Sleep Apnea Management Group Clinic on Positive Airway Pressure Adherence. (12th April 2019) - Tran, Katie; Wang, Lu; Mehra, Reena; Vanek, Robon; Kaw, Shivani; Moul, Douglas; Campean, Tina; Foldvary-Schaefer, Nancy; Walia, Harneet
Abstract: Introduction: Positive airway pressure (PAP) adherence is a critical focus for managing obstructive sleep apnea (OSA) which requires persistent monitoring and practical problem-solving. There are limited data on the impact of leveraging the group-based dynamic pertaining to PAP adherence. We postulate that our group-based approach, the Sleep Apnea Management (SAM) clinic, which harnesses the benefits of providing mutual support and understanding as well as facilitates access to system-based resources and education, will confer improvement to PAP adherence. Methods: 110 patients who attended SAM clinic from January 2017 to June 2018 were retrospectively analyzed. Baseline adherence data at the time of the SAM visit (median 1.7[0.19, 4.7] years from PAP set up) and 1-3 month follow-up from the baseline visit were collected. Average usage from all-days and days-used were analyzed along with demographics and co-morbidities. Adherence was defined as≥ 4 hours a night for≥ 70% of nights over a 30-day period. Absolute difference from baseline to 1-3 month follow-up adherence was compared using Wilcoxon signed rank test. Results: Average age was 60.9± 12.7 years, 52.7% were male, and 46.4% were Caucasian. At baseline, the median for average all-days usage was 4.73 hours; while that for average days-used usage was 5.63 hours; with the percentage-of-days usage≥ 4 hours being 64.5%. At follow-up, the median in average all-days usage increased 0.57 hours (p<0.001); while that for average days-used usage increased 0.31 hours (p<0.001); with the percentage-of-days with usage≥ 4 hours increasing by 4% (p<0.001). The percentage of patients at follow-up who met adherence criteria was 80.0%. Conclusion: With the SAM clinic intervention, the patient population significantly improved in all PAP adherence parameters. These results demonstrate how the novel, cost-effective SAM clinic model can be clinically impactful in improving PAP adherence. It provides group support and emphasizes the common tasks of educating and trouble-shooting barriers that would otherwise preclude full PAP usage and benefits. Further prospective studies with appropriate controls are needed to verify these findings and identify those individuals who are maximally responsive. Support (If Any)